INTERVAL ESTIMATION OF THE VOLUMES OF RESOURCE CONSUMPTION AT THE STOCHASTIC BASIC DATA - Y. Gagarin; S. Gagarina (Вестник университета, 2018)
The method of interval estimation of resource consumption volumes is considered with the random nature of a multitude of random factors. The necessity of taking into account errors in the values of functions and arguments when estimating the parameters of mathematical models is shown. To take into account the random nature of the initial information when estimating the parameters of the models, it is proposed to use methods of confluent analysis. A method has been developed that allows one to obtain point and interval estimates of model parameters, as well as interval estimates of functional dependencies with stochastic initial data. The developed method is used in predicting the volume of energy consumption at a housing and utilities complex enterprise.